Environmental Remediation Using Nanoparticles: A Review - Shamsuddeen, Ruslan; Adam, Ansar Bilyaminu; Mathew, Twan Sale; Abubakar, Musa Yahaya (Kwaghe International Journal of Sciences and Technology, 2024)
The use of nanoparticles for environmental remediation has gained significant attention in recentyears due to their unique properties and potential to revolutionize the field. This review providesa comprehensive overview of the current state of knowledge on the application of nanoparticlesfor environmental remediation, including the removal of heavy metals, pesticides, industrialeffluents, and other pollutants from water, soil, and air. The review discusses the various types ofnanoparticles used, including metal, oxide, and carbon-based nanoparticles, and theirmechanisms of action. The advantages and limitations of nanoparticle-based remediationtechnologies are also eval_uated, and future research directions are identified. The reviewhighlights the potential of nanoparticles to enhance the efficiency, sustainability, and cost-effectiveness of environmental remediation processes, and underscores the need for furtherresearch to fully realize their potential.